Effects of phase noise on subcarrier modulation performance over Malaga turbulence channel - Xizheng KE; Chenhao WANG; Dan CHEN (Tongxin xuebao)
The performance of wireless optical system employing subcarrier phase-shift keying modulation was researched,which was influenced by phase noise of system demodulator under on Malaga atmospheric turbulence channel.Combined Fourier series and MeijerG function properties,the probability density function of instantaneous signal to noise ratio in the Malaga turbulence model was got.The Fourier series of receiving signal phase and the closed form expression of symbol error probability were derived,which were in the wireless optical subcarrier shift keying modulation system.Under different modulation order and light intensity fluctuation variance,the influence of phase noise on the system symbol error rate was analyzed.The numeric results present that the system symbol error rate increases with the light intensity fluctuation variance when the phase noise is lower.When the phase noise is larger,the influence of modulation order is greater than of turbulence intensity to the error-rate floor appearing.And with the increasing of modulation order,the corresponding average signal to noise is lower when symbol error-rate floor appears.